Implementasi Senam Kaki Diabetik terhadap Penurunan Kadar Gula Darah pada Pasien DM Tipe II di Puskesmas Sering - Afiatika Ahsani; Atika Atika (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Type II diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, occurring due to abnormalities in insulin secretion, insulin action or both. One of the recommended sports exercises is leg exercises. Diabetic foot exercises are a form of physical exercise for Diabetes Mellitus sufferers of all ages to avoid injuries so that blood circulation in the feet can be facilitated. Foot exercises are movements that train the small muscles of the feet and improve blood circulation in various positions such as sitting, standing or lying down. The purpose of this writing is to discuss diabetes foot exercises which can reduce blood sugar levels in people with Type II Diabetes Mellitus. The writing method uses a descriptive design with a killing process approach. The written results show a decrease in blood sugar levels after carrying out diabetic foot exercises with results before doing 300 mg/dl and after doing 250 mg/dl.